Sexually transmitted infections and HIV in a rural community in the Lesotho highlands. Issue 1 (1st February 2000) - Colvin, M; Sharp, B
Abstract : Objectives: To conduct a knowledge, attitude, and practice (KAP) study and to determine the prevalence of sexually transmitted diseases (STDs), including HIV, in a community residing in remote, rural Lesotho. Methods: In 1995 a cross sectional, community based epidemiological study was conducted on a population of 7500 people living in 89 villages. A total of 29 villages were randomly selected and a systematic sample of houses within villages was obtained. Questionnaires were administered to subjects after written consent was obtained. Determination of N gonococcus and C trachomatis infection was done on urine using ligase chain reaction (LCR) technology. Using blood specimens, syphilis was diagnosed by RPR and TPHA tests and HIV by a single ELISA and confirmed with a western blot. Results: Questionnaires were administered to 277 women, 100 men, and 149 youths (12–15 years). Chlamydia was diagnosed in 28.4% of adults, gonorrhoea in 5.9%, syphilis in 11.3%, and HIV infection in 6.3%. All cases of HIV occurred along the main road (p=0.001) and 72% of individuals with gonorrhoea were co-infected with chlamydia (p = 0.0001). 11.6% of women and 38.0% of men had had sex with a non-regular partner in the past 3 months and none had used condoms. Conclusion: A high prevalence of STDs and HIV infection was found in a population characterised by low levels of knowledge about STD/HIV, high risk sexual behaviour, and evidence of inappropriate health seeking behaviour for STDs.